Exceso del consumo del tabaco y su incidencia de la bronquitis crónica en la comunidad del recinto san francisco del cantón Baba en el primer semestre del 2017 - Otacoma Santillan, Génesis Valeria (2017)
Bronchitis in inflammation of the bronchi that are ducts of the airways where the air passes to the lungs (hematosis), during bronchitis decreases the passage and exit of oxygen. During chronic bronchitis, the pleura is inflamed due to irritation caused by cigarette smoking and exposure to irritable substances, causing damage to the bronchi, hypersecretion of mucus, and difficulty in expelling it. In this project we used the field type methodology because we conducted surveys and interviews in the community which allowed us to get in direct contact with the affected people and descriptive because they explained the factors that cause chronic bronchitis, with the aim of analyzing the effects of excess tobacco consumption. In the San Francisco area of the Baba Canton, there is a high rate of excess consumption of tobacco and chronic bronchitis, the inhabitants of this community show disinformation about the effects of cigarette smoking on the respiratory system and the causes for chronic bronchitis. Trainings were developed for consumers of excess tobacco in order to provide basic information, understandable to improve their quality of life, good results were obtained because the inhabitants of San Francisco del Canton baba were able to understand the effects of the cigarette in The respiratory tract and taking precautions when smoking inside the home and around other people.